(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3HGJJ gehej JSQj WhGQbgG Coca Yjfqj hGdOeY SGHbgG deG CJGgG ef Gdjbjf hde Jcf JQGg jde WGQbgG s
(3BNQgG (B:s
(3MOKfj MSf Hf jMji Yf MeGO Yf BNQ UhJ VYg CHhg (B"(3dbO HNdJ(B" (3Ke eG VY TjFkG MJi eGJ ced GdSaQ GdKGdK ef cJGH GdLGeY GdcHjQ aj GdCZGfj s
(3ef fSNI QGHYIs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
Keywords: (3GdCOHs